2020
DOI: 10.1111/irv.12724
|View full text |Cite
|
Sign up to set email alerts
|

Human surveillance and phylogeny of highly pathogenic avian influenza A(H5N8) during an outbreak in poultry in South Africa, 2017

Abstract: Background: In June 2017, an outbreak of the highly pathogenic avian influenza A(H5N8) was detected in commercial poultry farms in South Africa, which rapidly spread to all nine South African provinces. Objectives:We conducted active surveillance for the transmission of influenza A(H5N8) to humans working with infected birds during the South African outbreak.Methods: Influenza A(H5N8)-positive veterinary specimens were used to evaluate the ability of real-time PCR-based assays to detect contemporary avian infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Although more than 10,000 people were estimated to have been exposed to HPAI viruses during the events from October 2016 to September 2018 (Adlhoch et al, 2019), no human infection with A(H5N6) or A(H5N8) viruses, as detected in wild birds and poultry in Europe, has been reported during the period covered by this report or previously Thornton et al, 2019). Also, a study following up and testing people exposed to infected birds during A(H5N8) outbreaks in South Africa did not report transmission to humans (Valley-Omar et al, 2020). One study of people exposed to infected or perished birds during the AI outbreaks between November 2016 and March 2017 did identify some individuals reactive for antibodies to A(H5N8) cla de 2.3.4.4 (Ilyicheva et al, 2018).…”
Section: Human Cases Due To A(h5n8) or A(h5n6) Viruses Detected In Eumentioning
confidence: 68%
“…Although more than 10,000 people were estimated to have been exposed to HPAI viruses during the events from October 2016 to September 2018 (Adlhoch et al, 2019), no human infection with A(H5N6) or A(H5N8) viruses, as detected in wild birds and poultry in Europe, has been reported during the period covered by this report or previously Thornton et al, 2019). Also, a study following up and testing people exposed to infected birds during A(H5N8) outbreaks in South Africa did not report transmission to humans (Valley-Omar et al, 2020). One study of people exposed to infected or perished birds during the AI outbreaks between November 2016 and March 2017 did identify some individuals reactive for antibodies to A(H5N8) cla de 2.3.4.4 (Ilyicheva et al, 2018).…”
Section: Human Cases Due To A(h5n8) or A(h5n6) Viruses Detected In Eumentioning
confidence: 68%
“…The mutation of T 160 A (H3 numbering) results in a lack of a glycosylation site at 158 and facilitates airborne transmission in ferrets [ 28 ]. The three polymerases of the H5N8 isolates from common cranes in this study were observed to exhibit L 89 V (in PB2), L 473 V (in PB1), and N 383 D, N 409 S, and S 515 T substitution (in PA), which contribute to enhanced viral replication in mammalian cell lines and serve as markers of mammalian adaptation [ 29 , 30 , 31 , 32 , 33 ]. The phenotype of increased virulence in mice with N 30 D, T 215 A (in M1), P 42 S (in NS), and M 105 V (in NP) mutations were also found in these strains [ 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 98%
“…Continued monitoring on the continent is highly relevant; a poultry farm that had been affected by the H5N8 HPAI outbreak in Mpumalanga Province, South Africa, in 2017, has once again been affected by this strain. This was discovered on 13 April 2021, after 300 birds died and tested positive for the strain [27,125]. These events underline the imminent threat of avian influenza zoonoses and the importance of monitoring the spread of the virus, particularly in countries that are underrepresented in studies and lie along the migration flyways of wild birds, as many parts of America, Asia, and Europe are extremely well studied.…”
Section: Discussionmentioning
confidence: 99%